Intervenciones textiles a partir de la iconografía de la cerámica de la cultura Cayambi - Tituaña Cumbal, Cynthia Paulina (2025)
The research project examines the iconography of the ceramics of the Cayambi culture through the application to textile design, contributes to fashion design with identity as a fundamental pillar in the development of the industry, also motivates more designers to participate, present works with the contributions offered by the country's heritage themes. It seeks to merge ancient ethnic designs with the combination of trends, to develop contemporary fashion items attractive to the public which encourages the acquisition of Ecuadorian products and designs, strengthening the ancestral identities, wearing clothing that not only involves covering the body, but also involves discovering a feeling or meanings that go beyond what can be perceived. The most outstanding icons were taken into account for redesign through Erwin Panofsky's methodology (preiconography, iconography and iconology), and a system of bipartitional laws was applied, and the harmonic tripartition of space was applied through Zadir Milla's harmonic tracing procedure, the decomposition of the icon to extract shapes, produce different modules and form a composition. A textile catalog was carried out to determine the feasibility of the proposal, in a variety of textile fabrics for use in various universes of clothing, using textile finishes such as prints, embroidery, sublimated, DTF and laser to iconographic patterns, are techniques that facilitate the creation of patterns to the designer to carry messages and meanings through the textile or clothing